175k views
5 votes
Pleaseee help guys:(

Pleaseee help guys:(-example-1
User Spirift
by
5.5k points

2 Answers

3 votes

Answer:


-√(3) /2

Explanation:

Note that this looks like the identity:

cos(A + B) = cosAcosB - sinAsinB.

In this case, A = π/12 and B = 3π/4. So, we can say that the given equation:

cos(π/12)cos(3π/4) - sin(π/12)sin(3π/4) = cos(π/12 + 3π/4) = cos(π/12 + 9π/12) = cos(10π/12) = cos(5π/6)

Ah, now we have a trigonometry problem we can easily solve!

cos(5π/6) = -cos(π/6) = -(√3)/2

Hope this helps!

User Eatcrayons
by
6.2k points
4 votes
≈0.524094
If you ever needed help with math you can download Photomath too that’s what I use
User George Aprilis
by
5.5k points